Given:-
[tex]25,22,19,16,\ldots[/tex]To find the nth term and the sum of first 20 terms.
So now we use the formula,
[tex]T_n=a+(n-1)d[/tex]So the value of a is the first term 25 and the value of d is,
[tex]d=22-25=-3[/tex]So the nth term is,
[tex]T_n=25+(n-1)(-3)[/tex]So the sum of terms formula is,
[tex]Sn=\frac{n}{2}\lbrack2a+\mleft(n-1\mright)d\rbrack[/tex]So substituting we get,
[tex]\begin{gathered} Sn=\frac{n}{2}\lbrack2a+(n-1)d\rbrack \\ S_{20}=\frac{20}{2}\lbrack2\times25+(20-1)(-3)\rbrack \\ S_{20}=10\lbrack50+(-3)(19)\rbrack \\ S_{20}=10\lbrack50-57\rbrack \\ S_{20}=10\lbrack-7\rbrack \\ S_{20}=-70 \end{gathered}[/tex]So the sum of terms is -70.